The answers are as follows,
B
D
C
C
B
Hope this helps.
Answer:
see explanation
Step-by-step explanation:
Given the recursive formula
=
and
= 2
=
, then
=
( multiply both sides by 4 )
a₃ = 4 ×
= 9
= 9 ( multiply both sides by 4 )
a₂ = 36
= 36 ( multiply both sides by 4 )
a₁ = 144
The first 4 terms are
144, 36, 9, 2 ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
Answer:
wz is the corresponding part
Step-by-step explanation:
Answer:
x = -7/2 multiplicity 2.
Step-by-step explanation:
4x^2 + 28x + 49 = 0
(2x + 7)(2x + 7) = 0
This is a perfect square.
2x + 7 = 0, so:
x = -7/2 multiplicity 2.
Answer: 7 x + 6 = 6 x minus 3
Step-by-step explanation:
- 2 (x + 3) + 5 x = 3 (2 x minus 1)
- Now you distribute.
- 2(x) + 2(3) = 2x+6
- And 3(2x) minus 3(1) = 6x minus 3
- 2x+6+5x = 6x minus 3
- Then combine like terms
- 2x +5x=7x and there are no other like terms on either side of the equation.
- 7x+6= 6x minus 3